Management Of Human Resources In Small Industry In Bandung District (Case Study Of Husna Hijab Bandung) - Fajar, Fitriani; Maria, Santi; Haryati, Risna (Program Pascasarjana STIE Amkop Makassar, 2023)
Human resources in a company is a valuable asset because it can affect the existence of an organization in the future. Each company has different management rules in creating good performance for its human resources. Good performance management will create high performance productivity in the organization. There are many factors that affect employee performance, including educational background and experience. Researchers formulate the problem on the impact of human resource management with the aim of measuring performance. This study aims to find out how human resource management affects employee performance. The research method used is descriptive quantitative which describes the data obtained from Husna Hijab Bandung. The results of the analysis show that the factors that influence performance,, effectiveness and independence. Kata Kunci: Educational background, experience, performance.